Analysis of The Effect of Service Quality and Price on Customer Loyalty Mediated by Customer Satisfaction at Al-Matuq Islamic Boarding School Laundry - Rini Aryani; Muh. Abdul Aziz; Muhammad Khairul Amal (PT. Maju Malaqbi Makkarana, 2026)
Customer loyalty is a crucial factor in maintaining the sustainability of any service business, including the laundry business. Al-Matuq Islamic Boarding School Laundry experienced a decline in turnover and frequency of repeated service usage during the 2023–2025 period, indicating a decline in customer loyalty. This study aims to analyze the effect of service quality and price on customer loyalty, with customer satisfaction as a mediating variable. The study used a quantitative approach with a survey method of 133 Al-Matuq Islamic Boarding School Laundry customers selected using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) assisted by AMOS 26. The results showed that service quality has a positive and significant effect on customer satisfaction (β = 0.647; p < 0.001), price has a positive and significant effect on customer satisfaction (β = 0.313; p = 0.002), price has a positive and significant effect on customer loyalty (β = 0.443; p < 0.001), and customer satisfaction has a positive and significant effect on customer loyalty (β = 0.197; p = 0.035). In contrast, service quality does not have a significant effect on customer loyalty (β = 0.077; p = 0.544). These findings indicate that customer satisfaction plays an important role in increasing customer loyalty, while service quality contributes more through increasing customer satisfaction than directly to loyalty. The implications of this study emphasize the importance of consistently improving service quality and setting prices that are in accordance with the benefits received by customers to increase customer satisfaction and loyalty in a sustainable manner